Immunomodulatory Activity of Chinese Betel (Peperomia pellucida L.) Extract on the Spleen Histopathology in a Murine Model of Gastroenteritis - Savitri, Lisa; Prasetyawan, Fendy; Saristiana, Yuneka; Meri, Meri; Mebung, Konradus Klala; Amanda, Cornelia (Biology, Medicine, & Natural Product Chemistry, 2025)
Gastroenteritis, a prevalent digestive disorder caused by various pathogens including Escherichia coli, remains a global health challenge with significant morbidity and mortality, particularly in low-income countries. The spleen, as a critical immune organ, is often compromised during systemic infections. Peperomia pellucida (L.) , a traditional medicinal herb, is known for its antimicrobial, anti-inflammatory, and antioxidant properties. This study investigates the histopathological effects of P. pellucida leaf ethanol extract on spleen tissue in mice induced with E. coli to model bacterial gastroenteritis. Thirty male Swiss mice were divided into six groups (n=5): normal control, negative control (aquades), positive control (Yakult), and three treatment groups receiving P. pellucida extract at 100, 300, and 500 mg/kg BW. After seven days of pretreatment, mice were orally infected with E. coli (1Ã—10â¶ CFU/mL) for another seven days. Spleen tissues were harvested, fixed, and stained with hematoxylin-eosin for histopathological evaluation focusing on degeneration, necrosis, and PMN infiltration. Statistical analysis was performed using ANOVA followed by LSD tests. The highest dose of P. pellucida extract (500 mg/kg BW) significantly reduced spleen tissue damage, showing decreased degeneration (9.08%), necrosis (6.05%), and PMN infiltration (18.45%) compared to lower doses. The effect was comparable to the positive control. The ethanol extract of P. pellucida demonstrates a dose-dependent protective effect on spleen histopathology in E. coli-induced gastroenteritis in mice, supporting its potential as a natural antiseptic agent.